TINGKAT KOHESI PERUMAHAN BERPAGAR TAMANDIPONEGORO, LIPPO KARAWACI, TANGERANG - Rani, Bethany Jaffa; Wiranegara, Hanny Wahidin; Taki, Herika Muhamad (Jurnal Lingkungan dan Kota, 2025)
Strong cohesion within a community is reflected in its residents, where they feel a strong sense of togetherness, frequently interact, and engage in activities with neighbors, showing a keen interest in staying in the area. Conversely, communities with low cohesion experience the opposite. Gated communities are often promoted as ideal environments for fostering community ties due to the social-economic homogeneity of residents and enhanced security. Additionally, there is a connection between the level of community cohesion and the willingness to report or intervene in criminal activities. This study aims to assess the level of cohesion in the gated community of Taman Diponegoro using the Housing Cohesion Instrument developed by Buckner (1988), known for its reliability. The research covers Taman Diponegoro and Rolling Hills, which feature similar housing designs and prices. The survey method, along with second-order confirmatory factor analysis (CFA) and scoring, was used. Out of 154 members in the WhatsApp group, 48 participated. Results show that cohesion is moderate, with residents rarely visiting each other. The large number of housing units, over 100, aligns with the rise of individualism. To improve cohesion, limiting the number of homes in gated communities is recommended.